Proposed Modification of the Policy on Provision of Consulting Services by the External Audit Firm. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2014)
At an informal Board meeting in January, there was broad support for removing the current blanket prohibition on the provision of non-audit-related consulting services by the Fund's external audit firm and replacing it with a blacklist approach, subject to robust safeguards to ensure the independence of the external audit firm. This paper makes specific proposals to implement such a change. This would align the Fund's policy on the provision of consulting services by the external audit firm with practices followed in major jurisdictions and allow the external auditor to perform certain consulting services with proper safeguards to maintain the auditor's independence. The proposed safeguards include: (i) a blacklist of prohibited services; (ii) an independence declaration by the external audit firm; (iii) limitations on the consulting fees that can be paid to the external audit firm; (iv) an oversight role for the External Audit Committee (EAC); and (v) review of consulting services provided by audit firms prior to the selection of a new external audit firm for the Fund. The staff sought the views of the EAC, which concurs with the proposal to modify the policy on the provision of consulting services by the external audit firm along with the related safeguards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet